Life after breast cancer: moving on, sitting down or standing still? A prospective study of Canadian breast cancer survivors - Sabiston, Catherine M; Wrosch, Carsten; Fong, Angela J; Brunet, Jennifer; Gaudreau, Patrick; O'Loughlin, Jennifer; Meterissian, Sarkis (Université d'Ottawa | University of Ottawa, 2018)
Introduction: Breast cancer (BC) is associated with serious physical and psychological health sequelae that affect quality and quantity of life. Physical activity (PA) and sedentary behaviour can prevent or diminish these sequelae; yet, little is known about how these lifestyle behaviours change after cancer treatment and if these changes affect post-treatment health. The first aim of this study is to describe natural trends in lifestyle behaviours (ie, PA, sedentary behaviour) in women treated for BC. The second aim is to examine the longitudinal associations between lifestyle behaviour changes and (1) physical health (eg, acute symptoms, chronic conditions, body composition, patient-reported fatigue, pain and functioning), (2) psychological health and illness (eg, depression, stress, affect, post-traumatic growth, cancer worry, mood, body image) and (3) biological functioning (eg, cortisol and C-reactive protein). The third aim is to examine modifiable self-regulation (ie, goal adjustment strategies) and motivation constructs (ie, self-determined regulations) that predict trends in lifestyle behaviours. Method and analysis: This is a prospective longitudinal study of 201 women treated for BC. Data (eg, surveys, accelerometers, saliva, blood) are collected every 3 months during the first year after women complete systemic treatment for a first diagnosis of BC, and once every year for 4 years thereafter. Data analyses assess trends and changes in PA and sedentary lifestyle behaviours, examine associations between these trends and changes in health outcomes and identify modifiable predictors of PA and sedentary lifestyle behaviours using multilevel modelling. Ethics and dissemination: Ethical approval was obtained from the University of Toronto (REB# 28180) and has been funded by the Canadian Institutes of Health Research (#186128). Study findings will be disseminated through peer-reviewed publications, academic conferences, local community-based presentations such as the Canadian Cancer Society and similar organisations.